2013
DOI: 10.1111/ceo.12247
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond‐laser application in intermediate AMD: 12‐month results of fundus appearance and macular function

Abstract: A single unilateral application of nanosecond laser to the macula produced bilateral improvements in macula appearance and function. The nanosecond retinal rejuvenation therapy laser warrants ongoing evaluation as an early intervention for AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 32 publications
2
63
1
4
Order By: Relevance
“…22,23,[25][26][27]29 When used at an energy setting similar to that used in the clinical trials for AMD, nanosecond pulsed laser treatment has been found to preserve retinal integrity in humans and mice. [28][29][30] In the present study, using both a clinically equivalent, subthreshold laser dose (0.065 mJ) and an in vivo fundus-OCT imaging method, we showed for the first time, to our knowledge, that retinal structure directly below the sites of laser treatment is normal. Specifically, at both 7 and 90 days after treatment there were no changes in outer nuclear layer thickness, the inner segment/outer segment/RPE complex, or in total retinal thickness directly under the laser treatment sites.…”
Section: Neuronal Integrity Is Preserved Directly Under Sites Treatedmentioning
confidence: 69%
See 3 more Smart Citations
“…22,23,[25][26][27]29 When used at an energy setting similar to that used in the clinical trials for AMD, nanosecond pulsed laser treatment has been found to preserve retinal integrity in humans and mice. [28][29][30] In the present study, using both a clinically equivalent, subthreshold laser dose (0.065 mJ) and an in vivo fundus-OCT imaging method, we showed for the first time, to our knowledge, that retinal structure directly below the sites of laser treatment is normal. Specifically, at both 7 and 90 days after treatment there were no changes in outer nuclear layer thickness, the inner segment/outer segment/RPE complex, or in total retinal thickness directly under the laser treatment sites.…”
Section: Neuronal Integrity Is Preserved Directly Under Sites Treatedmentioning
confidence: 69%
“…For the subthreshold setting, the nanosecond pulsed laser was applied at 0.065 mJ (irradiance: 52 mJ/cm 2 ) across five spots, which was calculated to be similar to clinical doses used in the human eye for the intervention in early AMD. 28,29 For the assessment of a suprathreshold energy setting, a single laser spot was applied at a dose of 0.5 mJ (irradiance: 398 mJ/cm 2 ), which is greater than the dose previously shown to result in retinal photoreceptor death. 29 …”
Section: Nanosecond Pulsed Laser Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…In two further trials carried out on patients with early AMD problems were identified with both the laser system and the trial design. The Australian trial 92 initially only delivered 12 lesions at clock hours around the macula. They noted clearance of drusen but no measurable change in visual acuity.…”
Section: Introductionmentioning
confidence: 99%